INFAQ FUND GOVERNANCE SYSTEM AND ITS EFFECTIVENESS ON THE PERFORMANCE OF ZAKAT MANAGERS IN BAITUL MAL BANDA ACEH, INDONESIA - Al Nasya Nurfajri; Nurdin Bakri; Yusriaina Yusuf (JURISTA: Jurnal Hukum dan Keadilan, 2022)
Baitul Mal is a financial institution that manages Muslim funds for social activities. The language is formal, objective, and value-neutral, and clear structure with logical progression is maintained. Grammatical correctness is observed, and precise word choice is employed when needed. This study aims to assess infaq fund governance policies and provisions, its impact on 'amil performance, and its compliance with Aceh Qanun No.10 of 2018. Descriptive analysis and Allocation to Collection Ratio (ACR) are the research methods employed. Technical term abbreviations are explained when first introduced and causal connections between statements are ensured. The author's research findings indicate that the implementation of governance in Baitul Mal of Banda Aceh City is carried out by the commissioners and the Shari'ah Supervisory Board in accordance with Qanun Aceh provisions. Their role is to assess, direct and monitor policies and provisions in accordance with the principles of 'amil governance to ensure effective implementation. (2) The ACR measurement indicates a 58% effectiveness rating, which is considered quite effective. The program's effectiveness is determined by activities that were not realized due to insufficient budget, despite the availability of adequate infrastructure for implementing planned activities. (3) The percentage of infaq funds managed by Baitul Mal exceeds the provisions outlined in Aceh Qanun No.10 of 2018 regarding Baitul Mal. The program's effectiveness is determined by activities that were not realized due to insufficient budget, despite the availability of adequate infrastructure for implementing planned activities. (3) The percentage of infaq funds managed by Baitul Mal exceeds the provisions outlined in Aceh Qanun No.10 of 2018 regarding Baitul Mal. Based on the preceding explanation, it is evident that Baitul Mal in Banda Aceh City has performed its responsibilities and functions proficiently.